Intention of university staf involvement in preventive maintenance programme: An analysis based on theory of planned behavior - Masitoh, Abu Hassan (2015)
The purpose of this study was to prove staff involvement and desire intention tendency for staff involved directly or indirectly in the preventive maintenance programed organize by the organization. In line with previous research, this paper explores the influence to get involved by using the theory of planned behavior and practice preventive maintenance policy in the workplace. It will prove whether there is influence behavior in preventive maintenance in the organization or not. The results show, to get involved and influence behavior between individual in preventive maintenance program exists among staff of the University. More than 80 percent (%) of the administrative staff that provide the response programmed of preventive maintenance and want to get involved in the program which was introduced by the University. This decision also shows that there are similarities and positive relationships in each individual behavior towards preventive maintenance program. Overall, the results are consistent with the preventive maintenance engagement. This study also documented the appropriateness of mechanisms to engage behind the behavior and therefore, it will add to the current knowledge of the existence of behaviors among university staff